Impact of Teamwork on Organizational Productivity in Nepalese Commercial Banks - Adhikari, Pitri Raj (Management Dynamics, 2020)
Teamwork is a critical component of team performance and requires an explanation of how a team behaves and it has the ability to enable the members of the team to have a higher level of emotional security, self-confidence and the ability to plan and decide with others positively. However, the benefits of teamwork for the employees are often more abstract and difficult to distinguish that may hamper organizational productivity. This study is an endeavor to extend the literature of impact on teamwork on organizational productivity in commercial banks. This paper attempts to examine the impact of teamwork on organizational productivity in Nepalese commercial banks. Structured questionnaires were distributed to 500 respondents of 27 Nepalese commercial banks but out of them only 350 responses are collected and are used for analysis. Descriptive and casual comparative research design are used to determine the relationship of organizational productivity (dependent variable) with independent variables (teamwork, team trust, working environment, training and development, and esprit de corps). Descriptive statistics and multiple regression models have been used to analyze the data. Organizational productivity is positively correlated with all independent variables and regression results exhibit significant and positive beta coefficients. It is observed that working environment is the most powerful factor for organizational productivity and employees’ satisfaction and training and development is the least influencing factor among all factors. Nepalese commercial banks also take into consideration team trust, teamwork, and espirit de corps because these factors have positive impact on organizational productivity. Nepalese commercial banks should focus on increase in prompt response to the team trust, appropriate training and development, better working environment, and proper teamwork to increase productivity.